Multiple Vesical Calculi Complicating Uterine Prolapsed - Basnet, P; Agrawal, A; Thakur, A; Uprety, D K; Bhatta, R; Koirala, S (Health Renaissance, 2015)
Vesical calculus associated with uterovaginal prolapse is very rare. We report a case of a 70–year –old multiparous lady with third degree uterovaginal prolapse for twenty years .Presence of multiple vesical calculus in the cystocele was noted on ultrasonography and x-ray pelvis while undergoing investigation for acute urinary retention. Vaginal hysterectomy with pelvic floor repair followed by suprapubic cystolithotomy was done in the patient. Multiple vesicle calculus were removed. Post operative course was uneventful. Bladder outlet obstruction resulting from prolapse is suspected to be the inciting factor in stone formation though the casual relationship between prolapse and vesical calculus is not established. DOI: http://dx.doi.org/10.3126/hren.v12i1.11989 Health Renaissance 2014;12(1):55-56